WAYS TO IMPROVE THE MANAGEMENT OF THE SECRETARY OF COMMERCIAL BANKS - kizi, Sharipova Makhliyokhon Bakhtiyor (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
In the article, the elements of capital of commercial banks, regulatory requirements for their adequacy are revealed based on econometric analysis. The state of capital of commercial banks is analyzed and practical proposals are made to improve the efficiency of income-generating assets.